406. Vancomycin Activity against Clostridioides difficile Over Three Decades in Chicago. (15th December 2022) - Skinner, Andrew M; Petrella, Laurica A; Young Kim, Do; Serna-Perez, Fidel; Johnson, Stuart
Abstract: Background: In 2017, the Infectious Diseases Society of America (IDSA) and Society for Healthcare Epidemiologist of America (SHEA) updated the C. difficile (CD) treatment guidelines recommending vancomycin as the preferred therapy for C. difficile infections (CDI). We assessed the in vitro vancomycin minimum inhibitory concentration (MIC) against CD across three decades to determine if the vancomycin MIC had increased since these guidelines were published. Methods: We performed antimicrobial agar dilution susceptibility testing on 89 clinically relevant CD isolates collected within Chicagoland area. These isolates were selected from 3 separate timeframes: 2005 – 2007, 2013 – 2015, and 2021. Isolates were selected based on the prevalence of restriction endonuclease analysis (REA) strain types within each time cohort. Treatment response to vancomycin was reviewed for patients from the 2021 cohort if CD isolates had a vancomycin MIC of ≥ 16 μg/ml. Results: The in vitro vancomycin geometric mean MIC against all 89 CD isolates was 2.53 μg/ml with a MIC50 of 2 μg/ml and MIC90 of 4 μg/ml. Comparing the 3 timeframes, the geometric mean vancomycin MICs from 2005-2007, 2013-2015, and 2021 were 2.35, 2.27, and 2.91, respectively (p=0.11). Comparison of the isolates collected from 2005 – 2015 to 2021, the in vitro vancomycin geometric mean MICs were 2.31 and 2.91, respectively (p = 0.037). REA group BI was the most common strain group to have an increased in vitro vancomycin MIC within the 2021 cohort as 4 of the 5 isolates tested had a MIC of 16 μg/ml. All 4 of the patients infected with these strains with an elevated vancomycin MICs were treated vancomycin. All 4 patients had a resolution of symptoms on vancomycin and 2 suffered from a recurrent infection within ≤4 weeks of completing vancomycin. Conclusion: The vancomycin MIC against CD has trended upwards slightly over the past 20 years. The most notable change occurred between 2015 and 2021. We hypothesize that this increase is due to increased use of oral vancomycin for the treatment of CDI. However, these data indicate that most isolates still have a MIC of ≤4 μg/ml and an elevated MIC does not appear to impact clinical outcomes. Further study is required to determine if this upward trend in vancomycin MIC continues and if this could have any potential clinical implications. Disclosures: Stuart Johnson, M.D., Ferring Pharmaceuticals: Membership on Ferring Publication Steering Committee|Ferring Pharmaceuticals: Employee|Summit Plc: Advisor/Consultant.